Reaching the end goal: Do interventions to improve climate information services lead to greater food security? - McKune, Sarah; Poulsen, Liz; Russo, Sandra; Devereux, Taryn; Faas, Simone; McOmber, Chesney; Ryley, Therese (Elsevier, 2018)
Climate change is projected to have profound effects on nutritional outcomes, particularly among children under five in developing countries, where small-scale, subsistence farming and livestock production supports a majority of livelihoods. An underlying mechanism by which climate change will negatively affect nutrition is through increased food insecurity, as both crop and livestock production are threatened by changing patterns of rainfall and temperature. Climate information services (CIS) provide short and long-term weather and climate forecasts through a variety of means with the aim of increasing smallholder farmers’ ability to cope and adapt to a changing environment. CIS can be used to increase climate-smart agriculture (CSA) practices, which in turn can increase agricultural productivity and farmer resilience, while simultaneously reducing greenhouse gas emissions. Through household surveys, focus group activities, and participant observation, this research investigates linkages between CIS, uptake of CSA practices, and household food security through investigation of four research sites, two in Senegal and two in Kenya. The research sites were selected based on their various levels of engagement in CIS programs sponsored by the CGIAR Research Program on Climate Change, Agriculture, and Food Security (CCAFS) at the time research was conducted. The role of gender dynamics in the relationship between CIS, CSA, and food security is also explored through 1) sex-disaggregated quantitative from household surveys, and 2) sex-disaggregated qualitative data focus groups, which focuses in part on conceptualization of women’s empowerment. Findings indicate that farmers are receiving CIS and are using that information to make changes in farming practices, without major differences between men and women. This research suggests that CCAFS-CIS interventions may be leading to adoption of CSA practices; however, no direct correlation between receipt of CIS and use of CSA practices was found, nor was a relationship established between use of CSAs and food security. These findings are inconclusive, however, given the near complete coverage of CIS and widespread food insecurity across sites. Importantly, participants did not ascribe their knowledge of CSA practices to CIS, and the important role of social and informal networks as a source of climate information emerges as an important area of additional exploitation for increased uptake of CSA for improved food security.